Structure with hydroxyapatite crystal layer and method for manufacturing the same
A fibrous composite with partially bonded hydroxyapatite layers on the fiber surface addresses the dispersion and biotoxicity issues of existing composites, providing stable biopolymer adsorption and separation without crosslinking agents, ensuring high adsorption capacity and easy handling.
Patent Information
- Application Number
- JP2021089911
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-05-28
AI Technical Summary
Existing composites of fibrous polymers with hydroxyapatite layers disperse in water and require crosslinking agents, which can cause biotoxicity, and lack efficient biopolymer adsorption and separation capabilities.
A method to produce a fibrous composite with a hydroxyapatite crystal layer on the fiber surface, where the layers are partially bonded, forming a cotton-like structure without using crosslinking agents, achieved by mixing fibers with a calcium solution, drying, and immersing in a phosphate solution to form a stable hydroxyapatite layer.
The composite maintains structural integrity in water, effectively adsorbs and separates biopolymers like proteins and viruses, and allows easy handling, with high adsorption capacity and mild desorption conditions.
Smart Images

Figure 0007664614000001 
Figure 0007664614000002
Abstract
Description
[Technical field]
[0001] This application relates to a structure that has a hydroxyapatite crystal layer on the surface of a fiber and is capable of adsorbing and separating biopolymers such as proteins, peptides, and viruses. [Background technology]
[0002] The development of materials that adsorb biopolymers such as proteins is important for applications in masks, air filters, water filtration filters, artificial bones, cell culture carriers, and virus adsorbents. Furthermore, the ability to desorb adsorbed biopolymers under mild conditions is important for applications in adsorption / separation materials such as carriers for liquid chromatography, column separation materials, and protein concentration materials for in vitro diagnostic reagents. Hydroxyapatite, a type of calcium phosphate ceramic, has attracted attention as a material that adsorbs biopolymers such as proteins.
[0003] In order to impart flexibility to this hydroxyapatite, a composite of fibrous polymer and hydroxyapatite has attracted attention. In order to apply the composite of fibrous polymer and hydroxyapatite as an adsorption / separation material, it is important that the surface of the fibrous polymer is covered with a thin and uniform layer of hydroxyapatite so that the contact area of the hydroxyapatite with the biopolymer increases. In addition, it is desirable for the composite to be cotton-like so that it can be easily handled by hand or with tweezers. Furthermore, when a biopolymer is adsorbed in water, it is desirable for the composite not to disperse in water in order to recover the biopolymer without using special equipment such as a centrifuge or a filter.
[0004] Patent Document 1 describes a composite in which a coating liquid containing hydroxyapatite microparticles, an aqueous urethane resin, and a self-emulsifying isocyanate compound is applied to nonwoven fibers. However, the composite in Patent Document 1 has a structure in which hydroxyapatite particles are attached to the nonwoven fibers. In other words, the hydroxyapatite particles only cover a part of the nonwoven fibers, and this composite has poor performance as an adsorbent.
[0005] Patent Document 2 describes a composite in which a fibrous polymer substrate is coated with a thin, uniform ceramic layer. This composite can impart chemical resistance, chemical resistance, oxidation resistance, wear resistance, corrosion resistance, and the like to the substrate, and can also provide the substrate with high fracture strength, high toughness, high toughness, high hardness, high elasticity, and functional gradient properties, and can achieve both lightness and strength. However, the composite of Patent Document 2 disperses when used in water because there is no bond between the fibrous polymer substrate or the composites themselves.
[0006] In order to use it in water, it is necessary to impart water insolubility to the fibrous polymer substrate or composite so that it does not disperse in water. To make the fibrous polymer substrate water insoluble, chemical methods such as crosslinking are often used. However, when a crosslinking agent is used for the fibrous polymer substrate, unreacted crosslinking agent or by-products caused by the crosslinking agent may cause biotoxicity, so a method for producing a composite without using a crosslinking agent is required. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2013-204209 A [Patent Document 2] International Publication No. 2018 / 143120 Summary of the Invention [Problem to be solved by the invention]
[0008] The objective of this application is to provide a structure that has a hydroxyapatite crystal layer on the surface of the fiber, which can adsorb and separate biopolymers such as proteins, peptides, and viruses, and is less likely to disperse in water. [Means for solving the problem]
[0009] The structure of the present application has a plurality of fibrous composites each including a fiber and a hydroxyapatite crystal layer provided on the surface of the fiber, and the hydroxyapatite crystal layers of the plurality of fibrous composites are partially bonded to each other to form a cotton-like structure. The adsorbent of the present application has the structure of the present application as a member for adsorbing biopolymers.
[0010] The method for producing a structure of the present application is a method for producing a structure having a fibrous composite comprising fibers and a hydroxyapatite crystal layer provided on the surface of the fibers, and includes a mixing step of mixing and stirring a dispersion liquid in which the fibers are dispersed with a first solution containing calcium ions to obtain a mixed liquid, a drying step of drying the mixed liquid to obtain a dried body comprising the fibers and calcium, and a structure formation step of immersing the dried body in a liquid and adding a second solution containing phosphate ions to obtain a structure. Effect of the Invention
[0011] In the structure of the present application, the hydroxyapatite crystal layers of the multiple fibrous composites are partially bonded to each other. Therefore, the structure of the present application hardly separates in liquid. The adsorbent of the present application has the structure of the present application as an adsorption member. Therefore, the adsorbent of the present application can adsorb biopolymers and easily separate the biopolymers as necessary. According to the manufacturing method of the structure of the present application, a structure having fibers and fibrous composites having a hydroxyapatite crystal layer provided on the surface of the fibers can be obtained without using a crosslinking agent, and hardly separates in liquid. [Brief description of the drawings]
[0012] [Figure 1] 1 is a transmission electron microscope image of the composite of Example 1. [Diagram 2] Graph showing the relationship between the equilibrium protein concentration and the amount of protein adsorption in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The structure, adsorbent, and method for manufacturing the structure of the present application will be described below based on the embodiment and examples. Note that duplicated explanations will be omitted as appropriate. In addition, when a numerical range is expressed by writing "~" between two numerical values, these two numerical values are also included in the numerical range. The structure of the embodiment of the present application includes a plurality of fibrous composites. The fibrous composite includes fibers and a hydroxyapatite crystal layer provided on the surface of the fibers. The fibers are thin and long materials, for example, the length of which is 100 times or more than the thickness.
[0014] The fiber may be a fibrous polymer. In an embodiment, the fiber is a fibrous polymer, and the fibrous polymer has an anionic functional group. Examples of the anionic functional group include, but are not limited to, a carboxyl group, a sulfo group, and a phosphate group. The fibrous polymer is preferably a polysaccharide. Examples of the polysaccharide include pectin, hyaluronic acid, cellulose, cellulose derivatives, and chitin chitosan derivatives such as carboxymethyl chitosan. Examples of the cellulose derivative include carboxymethyl cellulose, hydroxyethyl cellulose, TEMPO oxidized cellulose nanofiber, and hydroxypropyl methyl cellulose.
[0015] At least a part of the calcium or phosphate contained in the hydroxyapatite of the hydroxyapatite crystal layer is chemically bonded, such as by ionic bond, to the functional group on the surface of the fiber. In the embodiment, the calcium or phosphate present in the inner part of the hydroxyapatite crystal layer is chemically bonded to the functional group derived from the anionic group present on the surface of the fiber. Therefore, the hydroxyapatite crystal layer of the embodiment is not easily peeled off from the fiber and is not easily broken.
[0016] The thickness of the hydroxyapatite crystal layer is preferably 0.3 nm to 50 nm, more preferably 0.3 nm to 20 nm, and even more preferably 0.3 nm to 10 nm. In this way, since the hydroxyapatite crystal layer is thin, in the structure of the embodiment, the fiber can be endowed with the ability of hydroxyapatite to adsorb and separate biopolymers without impairing the lightness and flexibility of the fiber. That is, the adsorbent of the embodiment of the present application includes the structure of the embodiment as a member for adsorbing biopolymers, that is, as an active ingredient for adsorbing biopolymers. Examples of biopolymers include lysozyme and spike proteins such as viruses.
[0017] In the structure of the embodiment, a part of the hydroxyapatite crystal layer of a plurality of fibrous composites is bonded to each other. That is, the fibers or the fibrous composites are bonded to each other by the hydroxyapatite or the calcium contained in the hydroxyapatite. Therefore, the structure of the embodiment does not substantially disperse in water. "Does not substantially disperse in water" means that even if the entire structure is placed in water and ultrasonically cleaned for 10 minutes with an ultrasonic cleaner (manufactured by AS ONE, ASU-3M, oscillation frequency 42 kHz, output 80 W) that is widely used as a physicochemical device, a mass of the structure of 95% or more of the mass before ultrasonic cleaning can be picked up. In addition, the structure of the embodiment is cotton-like in which a plurality of fibrous composites are entangled with each other. Therefore, the structure of the embodiment has easy operability that allows it to be held by hand and used.
[0018] The structure of the embodiment can be obtained, for example, by chemically bonding the contact points between a plurality of fibers with calcium to form a cotton-like material, and then laminating a hydroxyapatite crystal layer on the surface of the cotton-like material. It is preferable that the laminated structure of this hydroxyapatite crystal layer is such that the hydroxyapatite is laminated in the c-axis direction toward the outside of the fiber, that is, the crystal plane of the surface of the hydroxyapatite crystal layer is the c-plane.
[0019] This is because the hydroxyapatite layers are stacked in the c-axis direction toward the outside of the fiber, making the hydroxyapatite layer stronger and enabling the fiber to be stably held. It is preferable that this stacked structure exists over the entire surface of the hydroxyapatite layer, for example, that the outermost shell of the ceramic crystal is composed of hydroxyapatite having a regular crystal structure.
[0020] The method for producing a structure according to an embodiment of the present application is a method for producing a structure having a fibrous composite including fibers and a hydroxyapatite crystal layer provided on the surface of the fibers, and includes a mixing step, a drying step, and a structure forming step. In the mixing step, a dispersion in which the fibers are dispersed is mixed with a first solution containing calcium ions and stirred to obtain a mixed solution. The fiber dispersion can be prepared by mixing the fibers with a dispersion medium and stirring, as necessary, using a propeller stirrer or a magnetic stirrer.
[0021] The dispersion is preferably an aqueous dispersion because it is easy to handle. Also, for the same reason, the first solution is preferably an aqueous solution. Examples of the first solution that is an aqueous solution include calcium nitrate tetrahydrate aqueous solution, calcium chloride aqueous solution, calcium chloride monohydrate aqueous solution, calcium chlorate dihydrate aqueous solution, calcium perchlorate aqueous solution, calcium bromide aqueous solution, and calcium acetate aqueous solution, but there is no particular limitation.
[0022] The calcium ion concentration of the first solution cannot be set in general because it must be changed depending on the concentration and amount of fiber. However, the calcium ion concentration of the mixture after mixing the fiber dispersion and the first solution is 1×10 -7 mol / L~2×10 -1 mol / L, preferably 1×10 -6 mol / L~2×10 -2 It is more preferable that the concentration is 0.1 to 1.0 mol / L. If the concentration is too high, the precipitation of calcium phosphate proceeds excessively in the structure formation step, making it difficult to form a thin, uniform hydroxyapatite crystal layer on the surface of the fibers.
[0023] In the drying step, the mixture is dried, for example, by pouring the mixture into a mold and drying it, to obtain a dried body that is a precursor of the structure. This dried body includes fibers and calcium. By drying, the functional groups of the fibers are bonded to the calcium, and the fibers can be bonded at their contact points. That is, in this dried body, at least a portion of the contact points between the fibers are chemically bonded by calcium to form a cotton-like structure. Note that this calcium is not an elemental metal, but a calcium component such as calcium ions. Examples of drying methods include heat drying using a dryer and freeze drying.
[0024] In the structure forming step, the dried body is immersed in a liquid, and a second solution containing phosphate ions is added to obtain a structure. At least one of the solvents of the liquid and the second solution is preferably water, since it is easy to handle. Examples of the second solution that is an aqueous solution include an aqueous solution of diammonium hydrogen phosphate, an aqueous solution of ammonium dihydrogen phosphate, an aqueous solution of disodium hydrogen phosphate, an aqueous solution of sodium dihydrogen phosphate monohydrate, an aqueous solution of sodium dihydrogen phosphate dihydrate, an aqueous solution of potassium phosphate, an aqueous solution of dipotassium hydrogen phosphate, an aqueous solution of potassium dihydrogen phosphate, and an aqueous solution of phosphoric acid, but there is no particular limitation.
[0025] The ratio of the amount of substance of calcium ions in the first solution to the amount of substance of phosphate ions in the second solution to be added, that is, the molar ratio, is preferably 0.1 to 20. This is because when the molar ratio of the hydroxyapatite crystal layer to be precipitated is 1.7 and the molar ratio of the materials is also approximately the same, the hydroxyapatite crystal layer can be precipitated efficiently. In addition, a dried body dried without adding the first solution to the fiber dispersion disintegrates when immersed in water. In contrast, a dried body dried after mixing the first solution with the fiber dispersion as in the embodiment does not disintegrate even when immersed in water for 24 hours.
[0026] In the structure forming step, it is preferable to leave the mixture to stand after adding the second solution. The time for leaving the mixture to stand is, for example, 10 minutes to 120 hours, and preferably 1 hour to 72 hours in order to promote the precipitation of calcium phosphate on the surface of the fiber. It is preferable to desalt the obtained structure by washing with water and then dry it. The method for producing a structure according to the embodiment can be carried out at room temperature and normal pressure, so that denaturation of the fiber can be suppressed and the load on the environment is small. Note that heating can be carried out in some or more steps as necessary.
[0027] The structure-forming step chemically bonds calcium ions and phosphate ions present on the surface of the precursor of the structure to form a hydroxyapatite crystal layer. After the structure-forming step, the first solution containing calcium ions and the second solution containing phosphate ions may be repeatedly added to the structure. Since the structure that has undergone the structure-forming step is substantially indispersible in water, a drying step between the addition of the first solution and the addition of the second solution is not required. In this way, a structure that does not contain unreacted crosslinking agent and by-products of the crosslinking agent is obtained. The absence of crosslinking agent and by-products of the crosslinking agent in the structure can be determined by component analysis, spectroscopic analysis, or color analysis using a reagent, etc. of the structure. EXAMPLES
[0028] Example 1 4.0 g of cellulose fiber (Dai-ichi Kogyo Seiyaku, Leocrysta I-2SX, 2 wt%) was dispersed in 16 mL of distilled water. 0.4 mL of 0.20 mol / L calcium acetate aqueous solution was added to this dispersion and stirred. 2 mL of the liquid after stirring was placed in a cylindrical container with an inner diameter of about 15 mm, and the solid content was freeze-dried to obtain a cylindrical cotton-like dried body with a diameter of about 15 mm and a thickness of about 10 mm. This dried body was immersed in 4 mL of distilled water, 0.08 mL of 0.12 mol / L diammonium hydrogen phosphate aqueous solution was added, and the mixture was left to stand at room temperature for 72 hours. After washing with distilled water to desalt, the mixture was freeze-dried to obtain a cotton-like structure with a diameter of about 15 mm and a thickness of about 10 mm.
[0029] This structure had a cotton candy or cylindrical cotton-like shape. A transmission electron microscope image of this structure is shown in Figure 1. It was found from Figure 1 that a uniform hydroxyapatite layer with a thickness of about 3 nm covered the surface of the fibrous polymer. In addition, the distance between the crystal planes of this hydroxyapatite crystal layer in the thickness direction was 0.34 nm, which indicated that the crystal plane on the surface of the hydroxyapatite crystal layer was a c-plane. From the shape of the structure and the transmission electron microscope image, it is considered that in this structure, multiple fibrous composites comprising cellulose fibers and hydroxyapatite crystal layers provided on the surfaces of the cellulose fibers are bonded to each other at parts of the hydroxyapatite crystal layers, and are entangled and cotton-like.
[0030] Example 2 The stability of the structure of Example 1 in water was evaluated. A cylindrical cotton-like structure with a diameter of about 15 mm and a thickness of about 10 mm was placed in a sample bottle, immersed in 3 mL of distilled water, and then dispersed for 10 minutes using an ultrasonic cleaner (ASU-3M, manufactured by AS ONE, oscillation frequency 42 kHz, output power 80 W (same below)). Even after this ultrasonic dispersion, the structure did not collapse and maintained a cylindrical cotton-like structure with a diameter of about 15 mm and a thickness of about 10 mm. The structure could be pinched with tweezers and removed from the sample bottle while maintaining this structure. The structure removed with the tweezers was freeze-dried, and the mass was measured to be 7.7 mg.
[0031] Since the mass of the structure of Example 1 before ultrasonic dispersion in water was 7.8 mg, it was found that 99% of the mass of the structure was retained even after ultrasonic dispersion in Example 2. That is, it was found that the structure of Example 1 has insolubility in water, in other words, the property of not dissolving in water and not dispersing in water. From this result, it is considered that in the structure of Example 1, the hydroxyapatite crystal layers of the multiple fibrous complexes are partially bonded to each other, that is, the hydroxyapatite crystal layers of the multiple fibrous complexes are partially integrated to each other, and the multiple fibrous complexes are entangled with each other.
[0032] Comparative Example 1 An aggregate of a composite having cellulose fibers and a hydroxyapatite crystal layer was obtained by the same procedure as in Example 1, except that after the calcium acetate aqueous solution was added, the diammonium hydrogen phosphate aqueous solution was added without freeze-drying. The aggregate was placed in a sample bottle, immersed in 3 mL of distilled water, and then dispersed in an ultrasonic cleaner for 10 minutes. The aggregate was uniformly dispersed in the water, and could not be removed from the water.
[0033] Example 3 Protein adsorption evaluation of the structure of Example 1 was carried out. 1 mL of a solution containing 0.3 mg of lysozyme was added to 3 mg of the structure, and the mixture was stirred for 24 hours in an incubator at an internal temperature of 4°C. The mixture was then centrifuged at 12,000 rpm for 5 minutes to precipitate the lysozyme adsorbed to the structure. The lysozyme concentration in the supernatant after centrifugation was quantified by the Bradford method, and the amount of lysozyme adsorbed to the structure was quantified from the concentration. The amount of lysozyme adsorbed per 1 mg of the structure was 93 μg, which means that 93% of the amount of lysozyme was adsorbed.
[0034] Comparative Example 2 For comparison, a commercially available hydroxyapatite crystal (Tahei Chemical Industry Co., Ltd., HAP-100, particle size 200 nm (hereinafter the same)) was evaluated for protein adsorption in the same manner as in Example 3. The amount of lysozyme adsorbed per mg of this hydroxyapatite crystal was 29 μg, which was 29% of the amount of lysozyme adsorbed.
[0035] Example 4 The maximum adsorption capacity of the protein to the structure of Example 1 was evaluated. 1 mL of each solution containing 0.5, 1.0, 2.0, 3.0, 4.0, or 5.0 mg of lysozyme was added to 1.5 mg of the structure. The lysozyme concentration was then quantified in the same manner as in Example 3. From these quantified values, an adsorption isotherm of lysozyme to the structure was created. Figure 2 shows the adsorption isotherm that shows the relationship between the equilibrium concentration of the protein and the amount of protein adsorption. The adsorption mode of lysozyme to the structure was well fitted to the Langmuir type, which indicates monolayer adsorption (coefficient of determination R 2= 0.97), and the maximum adsorption amount calculated from the Langmuir equation was 1667 μg per mg of the structure.
[0036] Comparative Example 3 For comparison, the maximum adsorption amount of lysozyme to commercially available hydroxyapatite crystals was calculated in the same manner as in Example 4. The maximum adsorption amount of lysozyme per 1 mg of the hydroxyapatite crystals was 57 μg.
[0037] Example 5 Protein desorption evaluation of the structure of Example 1 was carried out. The amount of lysozyme adsorbed to the structure was quantified in the same manner as in Example 3. Thereafter, the structure and the lysozyme adsorbed to the structure were taken out, immersed in phosphate buffer (pH 7.4) with a concentration of 0.01, 0.20, or 0.30 mol / L, and stirred for 24 hours in an incubator at an internal temperature of 4°C. Further, the structure was centrifuged at 12,000 rpm for 5 minutes, and the lysozyme concentration in the supernatant after centrifugation was quantified by the Bradford method, and the proportion of lysozyme desorbed from the structure was calculated.
[0038] When immersed in 0.10 mol / L phosphate buffer, the amount of lysozyme released was approximately 12%. In contrast, when immersed in 0.20 mol / L and 0.30 mol / L phosphate buffer, the amount of lysozyme released was approximately 93% and approximately 99%, respectively. Since the protein was released in a buffer near neutral pH 7.4, it was found that the protein could be released from the structure without denaturing it.
[0039] Example 6 The structure of Example 1 was evaluated for its adsorption of viral spike protein. 0.1 mL of a solution containing 5 μg of coronavirus (SARS-CoV-2) spike protein (Invitrogen, SARS-CoV-2 Spike Protein (S-RBD) (aa319-541) mFc Tag Recombinant Protein, RP-8770) was added to 2 mg of the structure and allowed to stand at room temperature for 1 hour. The concentration of the spike protein in the solution was then quantified by polyacrylamide gel electrophoresis (SDS-PAGE), and the mass of the spike protein adsorbed to the structure was quantified from the concentration. As a result, the mass of the spike protein adsorbed to 2 mg of the structure was 3.6 μg, indicating that 72% of the mass of the spike protein was adsorbed.
Claims
1. A plurality of fibrous composites each comprising a fiber and a hydroxyapatite crystal layer having a thickness of 0.3 nm to 50 nm provided directly on the surface of the fiber; The hydroxyapatite crystal layers of the plurality of fibrous composites are partially bonded to each other to form a cotton-like structure.
2. In claim 1, The structure is free of unreacted crosslinker and crosslinker by-products.
3. In claim 1 or 2, A structure that is substantially non-dispersive in water.
4. In any one of claims 1 to 3, A structure in which the crystal plane on the surface of the hydroxyapatite crystal layer is a c-plane.
5. In any one of claims 1 to 4, The structure wherein the fibers are cellulose fibers.
6. 6. An adsorbent having the structure according to claim 1 as a member for adsorbing a biopolymer.
7. In claim 6, The adsorbent, wherein the biopolymer is lysozyme or a viral spike protein.
8. A method for producing a structure having a fibrous composite including a fiber and a hydroxyapatite crystal layer provided on a surface of the fiber, comprising: a mixing step of mixing and stirring the dispersion liquid in which the fibers are dispersed with a first solution containing calcium ions to obtain a mixed liquid; a drying step of drying the mixture to obtain a dried body including fibers and calcium; a structure-forming step of immersing the dried body in a liquid and adding a second solution containing phosphate ions to obtain the structure; A method for manufacturing a structure having the above structure.
Citation Information
Patent Citations
Purified bone mineral particulate product
JP1992501070A
Calcium phosphate compound-cellulose fiber composite material and its production
JP1996260348A
Antimicrobial fiber and antimicrobial filtration material and their production
JP1998140472A
Antimicrobial fabrics, antimicrobial filter material and their production
JP1999256472A
Antibacterial fiber and antibacterial filter material, and their production
JP2000080560A